Microfinance and financial inclusion - Teki, S.; Mishra, R. K.; Institute of Public Enterprise (Hyderabad, India); Academic Foundation (New Delhi, India) (New Delhi : Academic Foundation in association with Institute of Public Enterprise, 2012)
The book states that the primary goal of financial inclusion is to broaden the scope of activities of the formal financial system, thus allowing people of low income to gradually participate in the system and thereby freeing the poor from poverty.
Includes bibliographical references (p. [307]-315).
ijb 26/02/2019
Keywords: Financial services industry; Microfinance; Finance